Rekonstruksi Maqasid Syariah: Relevansi dan Implementasinya dalam Konteks Hukum Islam Kontemporer - Muhammad Aldi Dahri; Ahmad Fadly Rahman; Ferdiansa Putra; Kurniati Kurniati (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2026)
Maqasid sharia is the foundation of Islamic law that needs to be reconstructed to remain relevant to the evolving times. Globalization, technological advancements, and social changes present new challenges, such as bioethics, digital economy, and social justice, which require a response from Islamic law. This article aims to analyze the reconstruction of maqasid sharia and its impact on the development of contemporary Islamic law. The research uses a qualitative approach through literature review and normative analysis. The findings show that the reconstruction of maqasid sharia should be carried out through a contextual reinterpretation of the objectives of sharia. This approach opens up broader space for ijtihad, ensuring that Islamic law remains relevant in addressing new issues. The reconstruction aims not only to align Islamic law with contemporary developments but also to strengthen its role in achieving justice and providing ethical solutions that meet the needs of modern society. Thus, Islamic law can continue to contribute to the advancement and well-being of humanity amidst global challenges.